Legal Relationship with Law No. 11 of 2020 Concerning Job Creation Using a Benefits Approach - M. Junaidi; Fitri Dzakiyya (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The main problem in this research is to examine the issue of the concept of Law Number 11 of 2020 concerning Job Creation Using a Beneficial Approach, regarding the view of Islamic Law regarding Law No. 11 of 2020 concerning Job Creation, benefits of Law no. 11 of 2020 concerning Job Creation for workers and the existence of Law no. 11 of 2020 concerning Job Creation from a Sharia Economic Law perspective. The type of research used in this research is library research. The data sources used are primary data and secondary data. The results of this research are that the review of Islamic law in Law no. 11 of 2020 concerning Job Creation is a form of preserving the soul (hifzh al-nafs) in the principles of maqashid sharia as a means of maintaining their economic rights to survive. As for the benefits of Law no. 11 of 2020 concerning Job Creation that can be felt at this time, namely: creating jobs, encouraging investment, an easier and faster licensing system, and simplified investment requirements. The value of Sharia Economic Law is viewed from Law no. 11 of 2020 concerning Job Creation, providing sharia economic growth, especially in the sharia financial industry in Indonesia such as Sharia Banks, Non-Bank Sharia Financial Industry, Sharia Cooperatives and Sharia Capital Markets, in the future there will be great opportunities in running their business.